TAX SETTLEMENT BOARD BILL. - Carey, John L. (The Accounting Review, 1949)
Tax Settlement board proposed by Representative Wilbur V. Mills of Arkansas, a member of the House Ways and Means Committee, would fill the place which was originally supposed to be occupied by the old Board of Tax Appeals. Mills' bill would also help to clarify and secure the position of certified public accountants in tax practice through its provision that anyone admitted to practice before the U.S. Treasury Department would automatically be admitted to practice before the Tax Settlement Board. As first planned in 1924, the Board of Tax Appeals was to have been an informal agency which would settle tax controversies with a minimum of delay and expense to the taxpayer. However, the bill creating the Board of Tax Appeals was amended before passage to require the use of formal rules of evidence in the Board's proceedings. With the burden of proof on tax payers who appealed their cases to the Board, this meant that such an appeal would almost certainly be costly and time consuming. As years went on, the Board of Tax Appeals became more and more like a court of law and its name was changed to U. S. Tax Court in 1942.